FLEXIBLE ELECTROMAGNETIC RADIATION SHIELDING CONSTRUCTIONS BASED ON CARBON CONTAINING FILLERS - T. A. Pulko; H. A. Ayad; A. M. Mohamed; L. M. Lynkou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The forming method of flexible electromagnetic radiation shielding constructions based on cells filling by the carbon containing materials is described. The frequency characteristics of electromagnetic radiation transmission and reflection coefficients in the range from 0.7 to 17 GHz of the designed constructions on the dependence of the utilized filler type are researched.